Oxidative Stress Assessment in Serum and Bronchoalveolar Lavage Fluid (BALF) of Normal and Pneumonic Sheep - Ajayi, John Olurotimi; Jarikre, Theophilus Aghogho; Usman, Abdulrauf Adekunle; Emikpe, Benjamin Obukuwho; Taiwo, Victor Olusegun (Universitas Airlangga, 2026)
Oxidative stress plays a critical role in the pathogenesis of respiratory diseases in small ruminants; however, a comprehensive assessment comparing systemic and local pulmonary oxidative status in naturally infected Nigerian indigenous sheep is lacking. This study evaluated oxidative parameters in serum and bronchoalveolar lavage fluid (BALF) from 210 sheep, including healthy controls and animals with naturally occurring pneumonia. Samples were analyzed for total protein, enzymatic antioxidants (glutathione peroxidase, glutathione transferase, superoxide dismutase), non-enzymatic antioxidants (reduced glutathione, vitamin C), and oxidative stress markers (myeloperoxidase, malondialdehyde, hydrogen peroxide, and nitric oxide). In pneumonic sheep, serum and BALF levels of glutathione peroxide, glutathione transferase, and superoxide dismutase were significantly reduced, whereas levels of myeloperoxidase, hydrogen peroxide, and nitric oxide were markedly increased. Malondialdehyde showed mild elevation. The most significant oxidative disturbances were observed in bronchopneumonia, bronchointerstitial pneumonia, and granulomatous pneumonia. These results demonstrate a pronounced oxidative imbalance in both the systemic and pulmonary compartments of sheep with pneumonia. Therefore, this study provides novel evidence supporting the integration of antioxidant therapy and targeted nutritional management into standard care protocols to mitigate oxidative damage and improve outcomes in pneumonic sheep.